Platô de São Joaquim, Província Magmática do Paraná: Feições de Campo e Questões Genéticas - Besser, Marcell Leonard; Vasconcellos, Eleonora Maria Gouvêa; Nardy, Antônio José Ranalli [UNESP] (My University, 2015)
The São Joaquim Plateau (SJP) is located in the Southern Highlands of Santa Catarina, which lays on the extreme southeast of the Brazilian Southern Highlands. The plateau is above Serra Geral Flood Basalts, which are organized mainly as pahoehoe flows, but also as a'a 'flows. The felsic rocks of SJP configure large tabular flows which thickness rises to 100 m and are widespread over 280 km2. Isolated hills in the plateau surroundings conserve remaining portions of these lava flows, evidence that their extension were much larger and is now reduced by erosion . The stratigraphy overlying basalt sequence is commonly architected as follows: (1) decametric level rocks of transitional character, represented by gray - reddish or red volcanites, massive toamygdaloidal, whichmaycontain decimetric geodes; (2)metric wavy level of amigdaloidal yellowish saprolite with stretched amygdales currently filled by white clays, autoclastic breccias formed by weathered pumice/scoria and pitchstone lenses; (3) basal decametric felsic level formed by pitchstone lenses and aphanitic rocks with banded laminar plane - parallel flow, twisted or folded flow; (4) decametric felsic level with platy joints; (5) thickness (< 65 m ) felsic level formed by thin phaneritic massive rocks, with or without tabular joints; (6) in the upper massive level appear rareamygdales. Due to lack of evidence to assign an ignimbritic genesis to these rocks, such volcanites of São Joaquim plateau are preliminarily designated as Plateau Rhyolites of the Serra Geral Formation.
São Joaquim Plateau, Paraná Magmatic Province: Field features and issues
Keywords: Lava stratigraphy; Paraná Province; Plateau rhyolites; São Joaquim plateau